Development of P5 Learning Module Theme Ecoprint in Middle School - Hakiki, Nurul; Ahmad, Abd Aziz; Irfan, Irfan (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The study's goal is to create a learning module project (P5) with an ecoprint theme to improve character in the application of independent dimensions and creative dimensions of students. This study uses research and development (R&D) and the 4D model scheme. The development of this 4-D model involved the steps of defining, designing, developing, and disseminating. Public Middle School 7 Makassar served as the study's site. The results of the study indicated that the assessment of the overall module by material experts obtained a value of 9.8 with an average of 4.9 with the description "Very Good," while the media expert assessed the quality of the module cover design, module content design, and aspects of media effects on learning strategies with a total value of 14.75 with an average of 4.9 and the description "Very Good." Based on the assessment of the material expert validator and the media expert validator, it can be concluded that the learning module project (P5) with an ecoprint theme is feasible to use. The intended final stage is dissemination; however, the researcher did not proceed to this stage. The final stage carried out was the teacher response test, which had previously been carried out on teacher needs testing. In addition, the results of this study also indicated that it made it easier for teachers or facilitators to transfer knowledge through interesting learning in the P5 ecoprint project learning theme.